Encapsulation of Lactiplantibacillus plantarum Using Lactoferrin and Alginate: Layer-by-Layer Coating and Dual Coating Air Brush Approaches for Enhanced Stability - Nora Idalia Diaz-Negrete; Gabriela Ramos Clamont Montfort; Cristina Cueto-Wong; Silvia Gabriela López-Fernández; Rene Renato Balandrán-Quintana (Dairy, 2025)
This study evaluated two techniques for encapsulating Lactiplantibacillus plantarum using bovine lactoferrin and sodium alginate. The first method involved a layer-by-layer (LbL) coating of lactoferrin and alginate directly onto individual cells, using three layers of these electrolytes. The second method focused on encapsulating the probiotics in calcium alginate miniaturized beads, followed by a lactoferrin coating (AAcL). Encapsulation efficiency was measured at 52.7% for the LbL method and 32.6% for AAcL. Encapsulation was confirmed through zeta potential changes and scanning electron microscopy (SEM) micrographs. After freeze drying, the LbL technique showed a 2.67 log CFU decrease in survival rates, whereas the AAcL method resulted in a 3.77 log CFU decline. Nonencapsulated probiotics experienced a reduction of 5.8 log CFU. In storage at −20 °C, the LbL method led to a 32% decrease in survival after 30 days and 41% after 90 days, while the AAcL method showed a decline of 15% after 30 days and 28% after 90 days. Both techniques preserved 75% of the initial L. plantarum population under simulated gastrointestinal conditions. Overall, these methods effectively protected the probiotic from environmental stress.